REFORMASI BIROKRASI MELALUI PROSES PELAYANAN SURAT KEMATIAN DAN RETREBUSI PEMAKAMAN DI DESA PATUMBAK I MELALUI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN DELI SERDANG - Geby Theresia; Mutia Febriana; Elsya Sonia; Dilpra Amartia; Wilson Albiner; Franklin Asido Rossevelt (Histeria Jurnal: Ilmiah Soshum dan Humaniora, 2022)
The purpose of this study was to determine the Bureaucratic Behavior in Death Certificate Services at the Office of Population and Civil Registry, and to find out the Funeral Retribution Service in Patumbak I Village, Deli Serdang. This study used descriptive qualitative method. While the data collection techniques used by researchers are observation, interviews and documentation. The results of this study indicate that the Bureaucratic Behavior in Death Certificate Services has referred to the Public Service Act Number 25 of 2009 concerning the Implementation of Public Services. However, the Deli Serdang Regency funeral retribution does not apply because it is not regulated in Deli Serdang Regency Regional Regulation No. 2 of 2012 concerning Public Service Retribution.